Hadith #4351 - Sunan Abi Dawud - Abdul 'Aziz bin Rafi' عبد العزيز بن رفيع; Aisha bint Abi Bakr; Ibrahim bin Tahman إبراهيم بن طهمان; Muhammad bin Snan bin Yazid محمد بن سنان بن يزيد; Ubaid bin 'Umayr bin Qatada عبيد بن عمير بن قتادة (Sunan Abi Dawud)
‘Ali burned some people who retreated from Islam. When Ibn ‘Abbas was informed of it, he said: If it had been I, I would not have burned them, for the Messenger of Allah (ﷺ) said: Do not inflict Allah’s punishment on anyone, but would have had killed them on account of the statement of the Messenger of Allah (ﷺ). The Apostle said: Kill those who change their religion. When ‘Ali was informed about it he said: How truly Ibn ‘Abbas said!
Grade: Sahih

Hadith #4994 - Sunan Abi Dawud - Abdul al-Kareem bin Malik عبد الكريم بن مالك الجزري أبو سعيد; Abdullah bin Shaqayq al-Aqayli عبد الله بن شقيق العقيلي; Ibrahim bin Tahman إبراهيم بن طهمان; Muhammad bin Snan bin Yazid محمد بن سنان بن يزيد; Muhammad bin Yahya bin Hiban محمد بن يحيى بن حبان (Sunan Abi Dawud)
The Messenger of Allah (May peace be upon him) was in the I’TIKAF(seclusion in the mosque). I came to visit him at night . I talked to him, got up and turned my back. He got up with me to accompany me. He was living in the house of Usamah b. Zaid. Two men of the Ansar passed by him. When they saw the Messenger of Allah (May peace be upon him), they walked quickly. The prophet (May peace be upon him) said: Be at ease; she is Safiyyah daughter of Huyayy. They said: Glory be to Allah, Messenger o
Grade: Sahih

Hadith #5003 - Sunan Abi Dawud - ibn Mas'ud; Muhammad bin Snan bin Yazid محمد بن سنان بن يزيد (Sunan Abi Dawud)
The Messenger of Allah (ﷺ) said: None of you should take the property of his brother in amusement (i.e. jest), nor in earnest. The narrator Sulayman said: Out of amusement and out of earnest. If anyone takes the staff of his brother, he should return it. The transmitter Ibn Bashshar did not say “Ibn Yazid, and he said: The Messenger of Allah (ﷺ) said.
Grade: Sahih